PENGENALAN TEKNOLOGI PENGOLAHAN KOMODITAS PERKEBUNAN BAGI SISWA SEKOLAH MENENGAH ATAS DI SAMARINDA KALIMANTAN TIMUR: Introduction To Plantation Commodity Processing Technology For Senior High School Students In Samarinda, East Kalimantan - M. Atta Bary; Edi Wibowo Kurniawan; Rudito Rudito; Andi Lisnawati; Ahmad Zamroni; Mujibu Rahman; Muh. Yamin; Elisa Ginsel Popang; Anis Syauqi; Netty Maria Naibaho; Hamka Hamka; Farida Aryani; Mika Debora Br Barus; Adnan Putra Pratama; Dody Purwanto; Supriono Supriono; Yuliana Sabarina Lewar; Silvia Darmans; Rindawati Rindawati (Pakis Journal Institute, 2023)
Higher education has a noble task, namely disseminating science and technology and cultural arts to all citizens with personal and institutional references to the principles of scientific methodology. Community capabilities need to be developed from various social strata by conveying the Tri Dharma of Higher Education, which is the main task of lecturers, this is a form of effort from universities to accelerate competitiveness to encourage the realization of government programs in national development. This community service activity is in collaboration with partners, namely high school and vocational schools (SMA / K) in Samarinda. The target of this program is to introduce and disseminate laboratory-based processing of plantation commodities at the Samarinda State Agricultural Polytechnic (PPNS) campus. From the results of observations in the field, there are still many high school / vocational students in Samarinda who are still not familiar with the processing technology of plantation commodities and the processing process and analysis techniques. The method of this activity is the delivery of material directly (lectures), discussion and deepening of the material by means of questions and answers, as well as simulation of laboratory-scale plantation commodity processing technology. The result of the implementation of this service is an increase in students' knowledge regarding plantation commodity processing technology and the students involved in this activity are able to master plantation commodity processing technology.